PERANAN BRAINWARE DALAM SISTEM INFORMASI MANAJEMEN - Rahmahwati Sidh (STMIK Mardira Indonesia, Bandung, 2015)
Management information system depends on the components in generating information systems that fit their needs. Gaps in the implementation of these components will be resulting in less accurate information, less detailed, less precise and less relevant time will result in errors in decision-making at the company or organization. Hence the need for a deep understanding of the components in the management of information systems in particular brainware is expected to produce valuable information in order for the company or organization in order to obtain sustainable competitive advantages. Keyword: brainware; information; information systems; management information system